2011
DOI: 10.1007/s00044-011-9578-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and antimicrobial activity of 4-amino-1-alkyl pyridinium salts

Abstract: A series of 4-amino-1-alkyl pyridinium bromide salts (1-10) were synthesized and antimicrobial activity was evaluated by disc diffusion as well as broth macro-dilution method. 4-Amino-1-hexadecylpyridinium bromide (10) which showed good inhibition against Candida albicans and C. glabrata also displayed good germ tube inhibition against C. albicans. Compound 8 shows very low haemolytic activity against human red blood cells. Compound 10 exhibits excellent antibacterial activity against Escherichia coli and Stap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…This result demonstrated that the compound 8 showed good antimicrobial activity and low toxicity to human red blood cells. Hence, it is suggested that the absence of or low level of haemolytic activity can be assumed to be the result of the absence of cytotoxic action, and this finding correlates with a previous report on 4-amino-1-alkyl pyridinium salts (Ilangovan et al, 2012).…”
Section: Haemolytic Activitysupporting
confidence: 88%
See 3 more Smart Citations
“…This result demonstrated that the compound 8 showed good antimicrobial activity and low toxicity to human red blood cells. Hence, it is suggested that the absence of or low level of haemolytic activity can be assumed to be the result of the absence of cytotoxic action, and this finding correlates with a previous report on 4-amino-1-alkyl pyridinium salts (Ilangovan et al, 2012).…”
Section: Haemolytic Activitysupporting
confidence: 88%
“…A homologous series of 1-alkyl-(N,N-dimethylamino)pyridinium bromides was prepared by adopting a procedure that has been used previously by us for the synthesis of 1-alkyl-4-aminopyridinium bromides (Ilangovan et al, 2012). Accordingly, a mixture of 4-N,N-dimethylaminopyridine (1 equiv.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aminopyridinium and 1-alkyl-aminopyridinium salts display a wide range of antimicrobial activity (Sundararaman et al, 2013;Ilangovan et al, 2012). They have found many applications such as surfactants (Gama et al, 1981), ionic liquids (Muldoon et al, 2010;Petkovic et al, 2011), liquid-crystal display mediums (Ezaki & Kokeguchi, 2006), ionic crystals for second-order non-linear optics (Anwar et al, 2001), phasetransfer catalysts in organic transformations (Kupetis et al, 2002) and additives for protein refolding processes (Yamamoto et al, 2011).…”
Section: Chemical Contextmentioning
confidence: 99%